X-ray reflectivity study of the heat shock protein Hsp70 interaction with an artificial cell membrane model - Makky, Ali; Czajor, Julian; Konovalov, Oleg; Zhakhov, Alexander; Ischenko, Alexander; Behl, Ankita; Singh, Shailja; Abuillan, Wasim; Shevtsov, Maxim (Scientific reports, 2023)
Membrane-bound heat shock protein 70 (Hsp70) apart from its intracellular localization was shown to be specifically expressed on the plasma membrane surface of tumor but not normal cells. Although the association of Hsp70 with lipid membranes is well documented the exact mechanisms for chaperone membrane anchoring have not been fully elucidated. Herein, we addressed the question of how Hsp70 interacts with negatively charged phospholipids in artificial lipid compositions employing the X-ray reflectivity (XRR) studies. In a first step, the interactions between dioleoylphosphatidylcholine (DOPC) in the presence or absence of dioleoylphosphatidylserine (DOPS) and Hsp70 had been assessed using Quartz crystal microbalance measurements, suggesting that Hsp70 adsorbs to the surface of DOPC/DOPS bilayer. Atomic force microscopy (AFM) imaging demonstrated that the presence of DOPS is required for stabilization of the lipid bilayer. The interaction of Hsp70 with DOPC/DOPS lipid compositions was further quantitatively determined by high energy X-ray reflectivity. A systematic characterization of the chaperone-lipid membrane interactions by various techniques revealed that artificial membranes can be stabilized by the electrostatic interaction of anionic DOPS lipids with Hsp70.
Gesehen am 22.10.2024